2007
DOI: 10.1021/jp074870f
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Metastable Nanocrystalline ZrW2O8 by a Melt-Quenching Method

Abstract: Metastable orthorhombic (γ) ZrW2O8 was obtained by fast cooling of the melt of a stoichiometric mixture of ZrO2 and WO3. Heating of the as-quenched sample at 600 °C for 15 h led to the full transition of the orthorhombic (γ) to the cubic (α) ZrW2O8 polymorph. The average crystallite sizes of the obtained ZrW2O8 phases were in the range of 50−80 nm. The morphology of the powdery products was characterized by scanning electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The melt quenching method is well known for the preparation of glassy or metastable phases and also for the design of the so-called glass ceramics [12][13][14]. The results reported by Morito et al [15] and our results published recently [16] showed that this method was appropriate for the preparation of cubic ZrW 2 O 8 and metastable orthorhombic (c) ZrW 2 O 8 . These results motivated us to extend the melt quenching method to the preparation of other phases with the same crystallographic structure.…”
Section: Introductionmentioning
confidence: 63%
“…The melt quenching method is well known for the preparation of glassy or metastable phases and also for the design of the so-called glass ceramics [12][13][14]. The results reported by Morito et al [15] and our results published recently [16] showed that this method was appropriate for the preparation of cubic ZrW 2 O 8 and metastable orthorhombic (c) ZrW 2 O 8 . These results motivated us to extend the melt quenching method to the preparation of other phases with the same crystallographic structure.…”
Section: Introductionmentioning
confidence: 63%
“…The small peak at about 2 θ = 24.5° was not from the α‐phase ZrW 2 O 8 . Perhaps it was caused by the impurity (possible WO 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…19,22 This phase transition is completely reversible, and the α-phase is restored upon cooling the material below the transition temperature. Zirconium tungstate begins decomposing into WO 3 and ZrO 2 after prolonged heating at 600 °C, 23 thus limiting the processing temperature for composite preparation. In addition, amorphization of the cubic α-phase is found to occur when high pressures are applied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Reported CTE values for this material vary between −8.7 ppm/°C and −9.1 ppm/°C up to about 160 °C. , If heated above this temperature, it undergoes a phase transition to a slightly disordered state (the cubic β-phase) that causes the CTE to increase, although the material still has a negative CTE (−4.9 ppm/°C). , This phase transition is completely reversible, and the α-phase is restored upon cooling the material below the transition temperature. Zirconium tungstate begins decomposing into WO 3 and ZrO 2 after prolonged heating at 600 °C, thus limiting the processing temperature for composite preparation. In addition, amorphization of the cubic α-phase is found to occur when high pressures are applied.…”
Section: Introductionmentioning
confidence: 99%